2007
DOI: 10.1111/j.1540-6237.2007.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Partisan Cross‐Pressure and Voter Turnout: The Influence of Micro and Macro Environments*

Abstract: This article explores the impact of the partisan homogeneity/heterogeneity of a variety of group environments on patterns of voter turnout for recent presidential elections in Erie County, New York. Copyright (c) 2007 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
2
17
1
Order By: Relevance
“…Feldman and Price (2008), for instance, showed that discussion leads to increases in political knowledge mainly when disagreement within discussion network is low. More directly pertinent to this study, a number of studies have demonstrated the negative impact of disagreement on participation (Belanger & Eagles, 2007;McClurg, 2006aMcClurg, , 2006bMutz, 2006).…”
Section: Impact Of Disagreement On Participation and Type Of Participmentioning
confidence: 97%
“…Feldman and Price (2008), for instance, showed that discussion leads to increases in political knowledge mainly when disagreement within discussion network is low. More directly pertinent to this study, a number of studies have demonstrated the negative impact of disagreement on participation (Belanger & Eagles, 2007;McClurg, 2006aMcClurg, , 2006bMutz, 2006).…”
Section: Impact Of Disagreement On Participation and Type Of Participmentioning
confidence: 97%
“…It is important to note that much of this current debate does not explicitly address households (for notable exceptions, see Bélanger and Eagles ; Bello and Rolfe ). Yet family or household members are regularly named as the most important or frequent discussion partners (Mutz , 126; Sinclair , 27).…”
Section: Social Influence In Partisan Householdsmentioning
confidence: 99%
“…The issue of social pressure on the decision making of youth is something of significant interest. Social pressures refer to the motivation to blend in with a group's norms, characteristics and attributes (Huang, Phau & Lin, 2008).According to Belanger and Eagles (2007), individuals exposed to contrasting views in their interpersonal relationships are likely to find themselves accountable to different constituencies, and therefore making it socially awkward for them to maintain strong views. Furthermore, the presence of a perceived threat from a source is likely to increase commonality and cohesion from the "threatened" group (Huang, Phau, & Lin, 2008).…”
Section: Social Pressuresmentioning
confidence: 99%